At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Type the correct answer in each box. Use numerals instead of words. If necessary, use / for the fraction bar(s).

Complete the inverse function for the function given below.

[tex]
\begin{array}{c}
f(x) = 2x - 4 \\
f^{-1}(x) = \square x + \square \\
\end{array}
\]


Sagot :

To find the inverse function of [tex]\( f(x) = 2x - 4 \)[/tex], we follow these steps:

1. Write down the function:
[tex]\[ y = 2x - 4 \][/tex]

2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to find the inverse:
[tex]\[ x = 2y - 4 \][/tex]

3. Solve for [tex]\( y \)[/tex]:
[tex]\[ x + 4 = 2y \][/tex]
[tex]\[ y = \frac{x + 4}{2} \][/tex]

4. Express the result in the form [tex]\( f^{-1}(x) = ax + b \)[/tex]:
[tex]\[ f^{-1}(x) = \frac{1}{2}x + 2 \][/tex]

Therefore, the completed inverse function is:
[tex]\[ f^{-1}(x) = 0.5x + 2 \][/tex]

So, in the blanks:
[tex]\[ f^{-1}(x) = \boxed{0.5} x + \boxed{2} \][/tex]